The framework for participation: A research tool for exploring the relationship between achievement and inclusion in schools - Black-Hawkins, Kristine (Derecho y Humanidades, 2014)
This article examines the Framework for Participation: a research tool established to support a recently completed study. The research was undertaken to explore the relationship between achievement and inclusion because headteachers and teachers in some schools continue to resist becoming more inclusive in their student intake on the grounds that doing so has a negative effect on the academic achievement of other students and will lower overall standards. Embedded in these professional concerns are a number of assumptions about the nature ofeducational inclusion and achievement, as well as how they affect each other and how they might be measured. Therefore, the aim of the research was to gain a nuanced understanding of the relationship between inclusion and achievement. As part of this work, the Framework was devised, providing a valuable structure for the collection, analysis, and presentation of detailedqualitative and quantitative data within a multi-site case study approach. The article explores the development of the Framework’s principles, purposes, and structure, and describes how it was used in the project. In doing so, it examines ways in which the use of the Framework in case study research is methodologically distinct from other studies with similar concerns and interests.